Structural and Electronic Influences on Rates of Tertpyridine−Amine CoIII−H Formation During Catalytic H2 Evolution in an Aqueous Environment. Issue 14 (10th June 2021) - DiMarco, Brian N.; Polyansky, Dmitry E.; Grills, David C.; Wang, Ping; Kuwahara, Yutaka; Zhao, Xuan; Fujita, Etsuko
Abstract: In this work, the differences in catalytic performance for a series of Co hydrogen evolution catalysts with different pentadentate polypyridyl ligands (L), have been rationalized by examining elementary steps of the catalytic cycle using a combination of electrochemical and transient pulse radiolysis (PR) studies in aqueous solution. Solvolysis of the [Co II −Cl] + species results in the formation of [Co II (κ 4 ‐L)(OH2 )] 2+ . Further reduction produces [Co I (κ 4 ‐L)(OH2 )] +, which undergoes a rate‐limiting structural rearrangement to [Co I (κ 5 ‐L)] + before being protonated to form [Co III −H] 2+ . The rate of [Co III −H] 2+ formation is similar for all complexes in the series. Using E 1/2 values of various Co species and p K a values of [Co III −H] 2+ estimated from PR experiments, we found that while the protonation of [Co III −H] 2+ is unfavorable, [Co II −H] + reacts with protons to produce H2 . The catalytic activity for H2 evolution tracks the hydricity of the [Co II −H] + intermediate. Abstract : Hydricity, hydricity, hydricity : A comparison of the elementary steps of a catalytic cycle used by a series of three hydrogen evolving Co catalysts in water revealed that differences in catalytic performance were ultimately driven by differences in the hydricities of the Co II −H forms.